2009
DOI: 10.1371/journal.pone.0008303
|View full text |Cite
|
Sign up to set email alerts
|

Nuclei of Non-Muscle Cells Bind Centrosome Proteins upon Fusion with Differentiating Myoblasts

Abstract: BackgroundIn differentiating myoblasts, the microtubule network is reorganized from a centrosome-bound, radial array into parallel fibres, aligned along the long axis of the cell. Concomitantly, proteins of the centrosome relocalize from the pericentriolar material to the outer surface of the nucleus. The mechanisms that govern this relocalization are largely unknown.MethodologyIn this study, we perform experiments in vitro and in cell culture indicating that microtubule nucleation at the centrosome is reduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 21 publications
1
33
0
Order By: Relevance
“…The rapid cell cycles in the developing embryo did not allow us to test whether increased incubation would result in mitotic events such as chromosome condensation or nuclear envelope breakdown that is predicted from classic cell fusion experiments [18]. Interestingly, a previous report found that the nuclear MTOC state of a muscle cell can convert the centrosome MTOC state of a U2OS cell, suggesting that, in some contexts, a non-centrosomal MTOC state can be dominant [28]. By combining photobleaching with cell fusion, we found that the SPD-2 adding onto the centrosome in the interphase cell following fusion conversion came only from the mitotic cell.…”
Section: Discussionmentioning
confidence: 98%
“…The rapid cell cycles in the developing embryo did not allow us to test whether increased incubation would result in mitotic events such as chromosome condensation or nuclear envelope breakdown that is predicted from classic cell fusion experiments [18]. Interestingly, a previous report found that the nuclear MTOC state of a muscle cell can convert the centrosome MTOC state of a U2OS cell, suggesting that, in some contexts, a non-centrosomal MTOC state can be dominant [28]. By combining photobleaching with cell fusion, we found that the SPD-2 adding onto the centrosome in the interphase cell following fusion conversion came only from the mitotic cell.…”
Section: Discussionmentioning
confidence: 98%
“…The dependence of myonuclear distribution on microtubules was originally inferred from pharmacological experiments and from correlative studies of nuclear position and the microtubule network (Englander and Rubin, 1987;Bruusgaard et al, 2006), and has more recently been shown by Cadot et al (2012) and Metzger et al (2012). Initial formation of microtubule filaments in myotubes might involve microtubule-nucleating activity on the nuclear surface (Tassin et al, 1985a;Bugnard et al, 2005;Fant et al, 2009). However, microtubules in our early differentiated C2C12 cultures were mostly seen in a parallel orientation along the length of the cell, with long microtubules running past nuclei instead of attaching end-on to their nuclear surface (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, nesprins and related proteins have been shown to interact with components of the microtubule network, such as kinesin, dynein and dynactin, and with the centrosome (Malone et al, 2003;Roux et al, 2009;Zhang et al, 2009;Zhou et al, 2009;Fridolfsson et al, 2010;Yu et al, 2011;Holzbaur, 2012, 2015). Several groups have reported that proteins of the centrosome, such as PCM-1, pericentrin and γ-tubulin, are relocated from the pericentriolar material to the nuclear envelope upon onset of myoblast differentiation, and that a substantial amount of microtubules grow from the nuclear surface following this reorganization (Tassin et al, 1985a;Bugnard et al, 2005;Srsen et al, 2009;Fant et al, 2009). In this study, we show that nesprin-1 is essential for the relocalization of centrosome proteins and components of microtubule motor complexes to the nuclear envelope in differentiating mouse myoblasts, and that nesprin-1 and the centrosome protein PCM-1 are needed for regular positioning of nuclei in these cells.…”
Section: Introductionmentioning
confidence: 99%
“…Required for stability of the cTuSC subunits c-tubulin, GCP2 and GCP3 (Fant et al, 2009b) Keratin Binds directly to GCP6 and assembles c-tubulin-containing nucleation sites in the apical domain of epithelial cells; interaction with GCP6 is disrupted by CDK1-dependent GCP6 phosphorylation (Oriolo et al, 2007) Augmin complex Enhanced interaction with cTuRC during mitosis; recruits cTuRC to spindle microtubules through GCP-WD to promote intra-spindle microtubule generation (Goshima et al, 2008;Lawo et al, 2009;Uehara et al, 2009;Zhu et al, 2008) …”
Section: Hca66mentioning
confidence: 99%